Beitrag zur automatisierten Handhabungsplanung komplexer Blechbiegeteile - Vormann, Bodo (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1995)
The aim of this thesis was the determination of methods for the automated planning of handling operations for complex bending parts. To reach this aim an object-oriented modelling technique was used. By means of this method models for the static, dynamic and functional behaviour of handling components were derived. One of the features of these models is their high degree of flexibility to describe multiple variations of commercial handling components offered by the manufactures. The derived model was accomplished and integrated in an planning system for die bending parts. This system also included a component for the planning of bending sequences. By means of this system a fully automatic and flexible production planning of the bending process has been made possible with consideration of handling aspect